Freedom of Religion or Belief Across the Commonwealth: Hard Cases, Diverse Approaches - Green, M. Christian (The review of faith & international affairs, 2018)
This paper addresses freedom of religion or belief (FoRB) issues that have been emerging in the Asian Commonwealth, including religious minorities, violent extremism, religion and development, rising secularism, and religious equality and around nondiscrimination. Pakistan and India have turned their attention to addressing the situation of minorities. Other nations, Bangladesh, with concerns about rising Islamism and secularism; Sri Lanka, with its legacy of inter-ethnic conflict; and Malaysia, with multiculturalism alongside religious protections, have recently advocated tolerance, respect, unity, harmony, and peace, even as interreligious tensions appear to be rising. This paper will examine the state of FoRB in these Commonwealth nations.